Optimization of Gene Design, PCR Assembly and Site-Directed Mutagenesis for the Synthesis of Beauveria Bassiana Protease Gene - Muhammad Azharuddin Azali; Salmah Mohamed; Azian Harun; Shaharum Shamsuddin; Muhammad Farid Johan (Journal of Sciences, Islamic Republic of Iran)
Synthetic gene construction is one of the components of synthetic biology. It can be used for various purposes such as to optimize gene expression. In this study, we proposed six predetermined criteria for designing oligos for the synthesis of the Beauveria bassiana protease gene. These criteria were set up to optimize the cost and to accommodate the oligos assembly. A total of 44 overlapping oligos were designed and synthesized 0.5 µM of oligos mixture was used in assembly PCR together with high fidelity DNA polymerase to produce 1.1 kbp fragment. The gene was visualized by agarose gel electrophoresis before subcloned into pCR™2.1-TOPO. The sequence of the gene was verified by DNA sequencing. Site-directed mutagenesis was performed to repair errors resulted from the gene synthesis. A sharp and distinguished band of the expected size of the protease gene was observed in agarose gel electrophoresis. Errors in the sequence which was detected by DNA sequencing were successfully repaired using our simplified site-directed mutagenesis protocol. The result indicated long DNA sequences (>1 kbp) can be synthesized with less error by using our method. Additionally, this method was easy to perform because it would require minimum optimization to synthesize other genes by following our guidelines.